Interference of poverty in menstrual hygiene management: A scoping review protocol (Research, Society and Development, 2024)
This article aims to present the scoping review protocol to map existing evidence in the literature and identify gaps regarding the interference of poverty in the management of menstrual hygiene. The methodology adopted will follow the Joanna Briggs Institute (JBI) method and the PRISMA Extension Scoping Reviews (PRISMA ScR) guidelines. The scoping review will be constructed in five stages: 1) Identification of the research question; 2) Identification of relevant studies; 3) Selection of studies; 4) Data extraction; and, 5) Summarization, analysis and presentation of data. The search will be carried out in the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrievel System Online (MEDLINE). The selected articles will be imported into Endnote and Rayyan software, in order to assist in organization and analysis. This protocol is registered with the Open Science Framework ensuring visibility of the review process.